Identifying predictors of early trial termination: a meta-epidemiological study utilising elements of the research ethics committee evaluation - Jansen, Marieke S.; Pet, Lodewijk A.; Buijs, Jeroen T.; Siegerink, Bob; Groenwold, Rolf H.H.; Dekkers, Olaf M. (Journal of clinical epidemiology, 2025)
Early trial termination remains frequent. Research ethics committees (RECs) could play a role in reducing the probability of early termination. Their review process provides a window for both identifying trials at high risk of terminating prematurely and imposing preventive measures, such as design modifications. This study aimed to explore whether characteristics of ethics review, alongside trial characteristics, are related to subsequent early trial termination. This meta-epidemiological cohort study assessed 198 clinical trials approved by a Dutch REC between 2015 and 2018. Data from archived trial protocols, related study documents, and correspondence between the REC and investigators were analysed to identify predictors of early termination during ethics review. Of the 198 trials, 69 (34.8%) terminated early, most often due to recruitment failure (n = 31, 35.2%). Several characteristics were associated with early termination, such as multicentre design (vs single centre, risk ratio [RR]: 1.89, 95% CI: 1.24–3.14), number of comments raised during ethics review (per comment, RR: 1.02, 95% CI: 1.00–1.05), and specific comments regarding privacy and confidentiality (RR: 1.21, 95% CI: 1.05–1.41) and participant information sheets (RR: 1.05, 95% CI: 1.02–1.08). Investigator sponsorship, longer review durations, and comments raised regarding privacy and confidentiality and subject selection were associated with an increased likelihood of recruitment failure, specifically. This exploratory study showed that various characteristics of ethics review have the potential to predict early trial termination. Further studies are needed to validate and expand upon these findings. Clinical trials sometimes end earlier than planned, often due to difficulties recruiting enough participants. When trials stop too soon, their results become less reliable. Research ethics committees (RECs) review trial plans before they begin to make sure they meet legal and ethical standards. RECs may also be able to help prevent early termination by identifying trials at high risk and recommending improvements. This study looked at 198 clinical trials approved by a Dutch REC to see if the characteristics of the ethics review process could predict which trials might stop early. The study found that about one-third of the trials ended early, most often due to recruitment problems. Trials were more likely to stop early if they involved multiple centres, received more comments from the REC, or received comments specifically about issues related to privacy, confidentiality, or the information given to participants. Recruitment problems were more common in trials that had longer review times, received comments about who was eligible to take part or issues related to privacy and confidentiality, or were run by researchers without commercial sponsorship. Overall, the findings suggest that by examining the ethics review process more closely, RECs might be able to identify and support trials at higher risk of stopping early. More research is needed to confirm these results and explore how RECs might help improve trial success. •Around one-third of clinical trials stop early, often due to recruitment failure.•Research ethics committees may help reduce the risk of early termination.•This study showed that aspects of ethics review can help predict early termination.•Review time, number and type of comments were linked to early trial termination.•Multicenter design was linked to termination and sponsorship to recruitment failure.